Fabricating consent for an ‘adjustment programme’: crisis narratives of economic journalists in Portugal - Almeida, J. R.; Castro Caldas, J.; Costa, A. (Journal of Greek Media and Culture, 2018)
Following Greece and Ireland, and preceding Spain and Cyprus, Portugal has been subject to a troika ‘adjustment program’ that lasted from mid-2011 to mid-2014. The implementation of the program was disturbed by ‘surprises’ stemming from its internal tensions, ‘exogenous’ shocks, resistance from the judicial system (the Constitutional Court), and opposition from large sections of the public. As in Greece, the program was experienced by most as a dramatic and traumatic event. Major actors in this drama have obviously been the troika institutions, the Portuguese government and its supporting parties, the Portuguese opposition parties, trade unions and other social movements. Other actors, namely journalists, arguably also played an important role. The research reported in this article is devoted to the role played by economic journalist during the ‘adjustment’ process. This research analyzed the content of the publications (op-eds) of some of the main Portuguese economic journalists prior to and during the period of implementation of the troika’s adjustment program. It surveyed all the publications (op-eds) of six authors between January 1, 2010 and July 30, 2014. The analysis of the journalist’s texts led to the following conclusions: a) the texts are rooted in a particular set of core (neoliberal) beliefs about the economy and its functioning – the ‘consensus view’; b) the crisis is perceived as an opportunity not to be missed to implement long due reforms aimed at approaching reality to the type of economy and society implicit in the ‘consensus view’; c) the texts were mainly concerned with deflecting opposition, or fabricating consent, to the ‘adjustment’.